Team Formation Using a Systems Thinking Approach. (20th August 2018) - Sanchez‐Segura, Maria‐Isabel; Hadzikadic, Mirsad; Dugarte‐Peña, German‐Lenin; Medina‐Dominguez, Fuensanta
Abstract : Team performance varies depending on the organization of their members, the exploitation of their synergies and their planning to optimally meet the minimum requirements with the best results. This article reports a dual‐purpose methodology. First, we use the soft systems methodology to start up viability‐driven teamwork based on team complexity, a better understanding of idiosyncrasy, and the synergies leveraging team behavior. The viable systems model is used to propose the essential functions of a team that effectively operates in dynamic organizational environments. Second, this research provides guidance for training teams to apply holistic thinking in their problem‐solving practice by helping them to co‐integrate and apply systemic approach for immersive problem solving. In essence, this article reports success drivers, generic teamwork structures and viability accomplishment references for agilely, effectively and synergistically launching teams. We wrap up by discussing the lessons learned from applying this approach to several teams and outline future developments. © 2018 John Wiley & Sons, Ltd.